2021
DOI: 10.3390/jcm10061213
|View full text |Cite
|
Sign up to set email alerts
|

What Effect Do Pulmonary Micronodules Detected at Presentation in Patients with Osteosarcoma Have on 5-Year Overall Survival?

Abstract: For osteosarcoma, staging criteria, prognosis estimates, and surgical recommendations have not yet changed to reflect increasingly sensitive computed tomography (CT) imaging. However, the frequent identification of micronodules (<5 mm) on presentation leaves clinicians in a difficult position regarding the need to biopsy, resect, or follow the lesions and whether to consider the patient metastatic or non-metastatic. Our objective was to compare the 5-year overall survival rates of patients with osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, the prognostic significance of these micronodules has not been fully established. Davison et al recently reported comparable 5‐year OS in patients with pulmonary nodules <5 mm at diagnosis compared to patients with no nodules, suggesting that surgery may not be necessary for micronodules identified at initial diagnosis 33 . However, this cohort of patients were therapy‐naïve with micronodules that likely responded to standard primary systemic therapies compared to those with relapse or progressive pulmonary disease that persisted after multiple systemic therapies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the prognostic significance of these micronodules has not been fully established. Davison et al recently reported comparable 5‐year OS in patients with pulmonary nodules <5 mm at diagnosis compared to patients with no nodules, suggesting that surgery may not be necessary for micronodules identified at initial diagnosis 33 . However, this cohort of patients were therapy‐naïve with micronodules that likely responded to standard primary systemic therapies compared to those with relapse or progressive pulmonary disease that persisted after multiple systemic therapies.…”
Section: Discussionmentioning
confidence: 82%
“…identified at initial diagnosis. 33 However, this cohort of patients were therapy-naïve with micronodules that likely responded to standard primary systemic therapies compared to those with relapse or progressive pulmonary disease that persisted after multiple systemic therapies. In contrast, Ahmed et al performed a retrospective study in 125 patients with metastatic OST (48 with initial lung metastases at diagnosis and 77 with delayed lung metastases), and reported that patients with high ratio (>1) of surgically resected (SR) to radiologically detected (RD) OST pulmonary nodules (SR/RD) were associated with poor survival compared to patients with low ratio of SR/RD.…”
mentioning
confidence: 99%
“…[83][84][85] Surgical sampling is undertaken in some centers, but its value in determining overall survival and guiding treatment is unproven. 84,86 Data support the use of 18F-fluorodeoxyglucose positron emission tomography with computerized tomography (FDG-PET/CT) scanning both for accurate staging, especially of the skeleton, and for determining response to chemotherapy in selected patients. [87][88][89] Approaches to follow-up after treatment vary in visit intervals, pulmonary imaging modalities, and monitoring for late effects of treatment.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Although only 20% of patients have clinically evident metastases at onset, sensitivity of cross‐sectional imaging demonstrates 30%‐45% have pulmonary nodules of uncertain clinical significance that do not meet defined COG criteria for metastases and about one third of these progress to metastatic disease 83–85 . Surgical sampling is undertaken in some centers, but its value in determining overall survival and guiding treatment is unproven 84,86 . Data support the use of 18F‐fluorodeoxyglucose positron emission tomography with computerized tomography (FDG‐PET/CT) scanning both for accurate staging, especially of the skeleton, and for determining response to chemotherapy in selected patients 87–89 …”
Section: Areas Of Clinical Uncertainty For Ayasmentioning
confidence: 99%
“…[84][85][86] Surgical sampling is undertaken in some centers but its value in determining overall survival and guiding treatment is unproven. 85,87 Data to support the use of FDG-PET/CT scanning both for accurate staging, especially of the skeleton, and to determine response to chemotherapy, supports its use in selected patients. [88][89][90] Approaches to follow-up after treatment vary in visit intervals, pulmonary imaging modalities and monitoring for late effects of treatment.…”
Section: Osteosarcomamentioning
confidence: 99%